Habitual exercisers versus sedentary subjects with Parkinson's Disease: Multimodal PET and fMRI study - Sacheli, Matthew A.; Murray, Danielle K.; Vafai, Nasim; Cherkasova, Mariya V.; Dinelle, Katie; Shahinfard, Elham; Neilson, Nicole; McKenzie, Jessamyn; Schulzer, Michael; Appel‐Cresswell, Silke; McKeown, Martin J.; Sossi, Vesna; et al. (Movement disorders, 2018)
ABSTRACT Background The benefits of exercise in PD have been linked to enhanced dopamine (DA) transmission in the striatum. Objective To examine differences in DA release, reward signaling, and clinical features between habitual exercisers and sedentary subjects with PD. Methods Eight habitual exercisers and 9 sedentary subjects completed [11C]raclopride PET scans before and after stationary cycling to determine exercise‐induced release of endogenous DA in the dorsal striatum. Additionally, functional MRI assessed ventral striatum activation during reward anticipation. All participants completed motor (UPDRS III; finger tapping; and timed‐up‐and‐go) and nonmotor (Beck Depression Inventory; Starkstein Apathy Scale) assessments. Results [11C]Raclopride analysis before and after stationary cycling demonstrated greater DA release in the caudate nuclei of habitual exercisers compared to sedentary subjects (P < 0.05). Habitual exercisers revealed greater activation of ventral striatum during the functional MRI reward task (P < 0.05) and lower apathy (P < 0.05) and bradykinesia (P < 0.05) scores versus sedentary subjects. Conclusions Habitual exercise is associated with preservation of motor and nonmotor function, possibly mediated by increased DA release. This study formulates a foundation for prospective, randomized controlled studies. © 2018 International Parkinson and Movement Disorder Society